National Geographic Information Infrastructure: A Perspective View - Sharma, Rabin Kaji (Journal on Geoinformatics, Nepal, 2002)
The aim of this paper is to discuss the nature, concept and to provide a perspective view of National Geographic Information Infrastructure [NGII]. The objective of NGII is to integrate the existing data and also data that will be generated in future from various sources and to disseminate the same to the users in a Clearinghouse concept, in which the leading organizations should design a new working policy framework, coordinate the organizations involved in the programme and to provide standard data/information. With this, the country will benefit economically as it will minimize the data duplication and in the mean time maximize the data sharing. Finally, the paper recommends the activities to be initiated for the development of NGII.